PENGARUH LITERASI KEUANGAN, GAYA HIDUP DAN PENDAPATAN TERHADAP KEMAMPUAN PENGELOLAAN KEUANGAN PRIBADI SISWA/I SMA NEGERI 87 JAKARTA SELATAN - Nizami, Fadlan; Basir, Abdul; Sukrisno, Andy (Journal MISSY (Management and Business Strategy), 2025)
This study aims to analyze the effect of financial literacy, lifestyle, and income on personal financial management among students of SMA Negeri 87 Jakarta Selatan. The problem addressed is how these factors influence Generation Z’s financial behavior in managing pocket money. The research applied a quantitative approach using multiple linear regression with 88 respondents. Partial tests show that financial literacy has a significant effect (β = 0.257; t = 3.431; Sig = 0.001), lifestyle has a significant effect (β = 0.599; t = 10.152; Sig = 0.000), and income also has a significant effect (β = 0.027; t = 3.677; Sig = 0.000). The simultaneous test obtained F = 71.248 with Sig F = 0.000 and Adjusted R² = 0.708, indicating that the three variables explain 70.8% of personal financial management variation. These findings highlight the importance of financial literacy and lifestyle control in shaping healthy financial habits. Keywords : Financial Literacy, Lifestyle, Consumer Behavior, Financial Management, Generation Z.